Social participation in the unified health system of Brazil: an exploratory study on the adequacy of health councils to resolution 453/2012 - Rita de Cássia Costa da Silva; Maykon Anderson Pires de Novais; Paola Zucchi (BMC, 2021)
Abstract Introduction Social participation is one of the guidelines of the Brazilian health system. Health councils are collegiate instances of participation established by Law 8.142/90. The most recent legal regulation for council organization and functioning was established through Resolution 453/2021. The institution of health councils has a permanent and deliberative nature to act in the formulation, deliberation and control of health policy implementation, including in economic and financial aspects. Objective To evaluate the compliance of health councils with the directives for the establishment, restructuring and operation of the councils from Brazil, based on Resolution 453/2012. Methods An exploratory, descriptive study that used the Health Council Monitoring System as a data source. Qualitative variables were selected to identify the characteristics related to the councils' establishment (legal instruments for establishment), the strategies adopted for restructuring (budget allocation, existence of an executive secretariat, provision of a dedicated office) and the characteristics of the health councils' operation (frequency of regular meetings, existence of a board of directors, the election of the board of directors). Results The study analyzed three groups of characteristics related to the constitution, strategies adopted for restructuring and the functioning of the councils. Regarding the constitution of the councils, the findings revealed that the vast majority was constituted in accordance with the legislation and, therefore, is in compliance with Resolution 453/2021. In the second group of characteristics that describe the restructuring of councils, the study found that less than half of registered councils are in compliance with the standard. And, finally, in the third group of characteristics, it was found that the boards have adopted different frequencies for regular meetings and approximately 50% of the boards studied have a board of directors. Conclusions The councils still do not meet the minimum conditions necessary to fulfil their role in the Unified Health System (SUS), as stipulated in Resolution 453/2021. This situation requires monitoring by public oversight agencies. Despite the increase in popular participation with the creation of the health councils, this study demonstrated that most councils still do not meet the minimum conditions for monitoring public health policy. The improvement of the Health Councils Monitoring System (SIACS) to become an instrument for monitoring the councils, with the definition of goals and results, may contribute to the organization of the councils and, therefore, to the realization of social participation in Brazil.